Role of CCL-2, CCR-2 and CCR-4 in cerulein-induced acute pancreatitis and pancreatitis-associated lung injury. Issue 5 (23rd February 2011) - Frossard, Jean Louis; Lenglet, Sébastien; Montecucco, Fabrizio; Steffens, Sabine; Galan, Katia; Pelli, Graziano; Spahr, Laurent; Mach, Francois; Hadengue, Antoine
Abstract : Background and aims: Acute pancreatitis is an inflammatory process of variable severity. Leucocytes are thought to play a key role in the development of pancreatitis and pancreatitis-associated lung injury. The interactions between inflammatory cells and their mediators are crucial for determining tissue damage. Monocyte chemoattractant protein-1 (or CCL-2), CCR-2 and CCR-4 are chemokines and chemokine receptors involved in leucocyte trafficking. The aim of the study was to evaluate the role of the CCL-2, CCR-2 and CCR-4 chemokine receptors in the pathogenesis of cerulein-induced pancreatitis and pancreatitis-associated lung injury. To address the role of CCL-2, CCR-2 and CCR-4 that attracts leucocytes cells in inflamed tissues, pancreatitis was induced by administering supramaximal doses of cerulein in mice that do not express CCL-2, CCR-2 or CCR-4. Methods: The severity of pancreatitis was measured by serum amylase, pancreatic oedema and acinar cell necrosis. Lung injury was quantitated by evaluating lung microvascular permeability and lung myeloperoxidase activity. Chemokine and chemokine-receptor expression were quantitated by real-time PCR. The nature of inflammatory cells invading the pancreas and lungs was studied by immunostaining. Results: The authors have found that pancreas CCL-2 and CCR-2 levels rise during pancreatitis. Both pancreatitis and the associated lung injury are blunted, but not completely prevented, in mice deficient in CCL-2, whereas the deficiency in either CCR-2 or CCR-4 does not reduce the severity of both the pancreatitis and the lung injury. The amounts of neutrophils and monocyte/macrophages (MOMA)-2 cells were significantly lower in mice deficient in CCL-2 compared with their sufficient littermates. Conclusions: These results suggest that CCL-2 plays a key role in pancreatitis by modulating the infiltration by neutrophils and MOMA-2 cells, and that its deficiency may improve the outcome of the disease.